4(d+2x)-5=3(3x+7)

Simple and best practice solution for 4(d+2x)-5=3(3x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(d+2x)-5=3(3x+7) equation:


Simplifying
4(d + 2x) + -5 = 3(3x + 7)
(d * 4 + 2x * 4) + -5 = 3(3x + 7)
(4d + 8x) + -5 = 3(3x + 7)

Reorder the terms:
-5 + 4d + 8x = 3(3x + 7)

Reorder the terms:
-5 + 4d + 8x = 3(7 + 3x)
-5 + 4d + 8x = (7 * 3 + 3x * 3)
-5 + 4d + 8x = (21 + 9x)

Solving
-5 + 4d + 8x = 21 + 9x

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 4d + 5 + 8x = 21 + 5 + 9x

Reorder the terms:
-5 + 5 + 4d + 8x = 21 + 5 + 9x

Combine like terms: -5 + 5 = 0
0 + 4d + 8x = 21 + 5 + 9x
4d + 8x = 21 + 5 + 9x

Combine like terms: 21 + 5 = 26
4d + 8x = 26 + 9x

Add '-8x' to each side of the equation.
4d + 8x + -8x = 26 + 9x + -8x

Combine like terms: 8x + -8x = 0
4d + 0 = 26 + 9x + -8x
4d = 26 + 9x + -8x

Combine like terms: 9x + -8x = 1x
4d = 26 + 1x

Divide each side by '4'.
d = 6.5 + 0.25x

Simplifying
d = 6.5 + 0.25x

See similar equations:

| 7x-15=5x+7 | | 2c-5=c+9 | | x+x+81=x+144 | | -6+3w=-21 | | -6t-12-6t=10(t+5)+4 | | 2[1-3(w+2)+2(w+3)]=5w | | x-5-(-2)+2x=7 | | Q-2.4=1.8 | | 3b=6v+3b | | 10y+18=-3(5y-7)+5y | | 4n^2-4n-6=0 | | K-56=107 | | y+5=-7x-21 | | x^2-y^2-3x+3= | | x+x+2+x+2=75 | | (x^2-2x-1)+(2a^2+2a+3)= | | 3g+2(-5+2g)=1-g | | 2(a+1)+4a=-10 | | x^2(x^2+x+1)=0 | | 8(p+1)-6p=24 | | 5(x+4)=3x+14 | | 625=(x^2)+(x^2)+6x+9 | | 9k-32=6k+8 | | x/7=5 | | 12x+7y=-35 | | x^3+125y^3= | | k+3(3)=45 | | 500-3x=275 | | 6(-1-d)=-42 | | n-10=.3n-7-.3n | | (3u+7)(6-u)=0 | | 2-11-19= |

Equations solver categories